Non-self Psychology: The Buddhist phenomenology of self experience: A follow-up article to The Subject Matter of Psychology: Psyche, Dasein, non-self (Existential Analysis, 31.2) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
Understanding that the essential subject matter of psychology is not an object, thing or self-enclosed entity, this article presents the Buddhist psychology of non-self as a phenomenology of self-experiencing. Through the dizzying interaction of five psychic constituents (skandhas), emotional reactivity and mental fixation reify a self-entity where there is none.
Keywords: Buddhism; aggregates; psyche; self; phenomenology; non-self; psychology; skandhas